Diversity and Potential of Flowering Plants in Timau Mutis Nature Reserve, Tasinifu Village - Ite Morina Yostianti Tnunay; Florian Mayesti Prima R. Makin; Welsiliana Welsiliana (Universitas Muhammadiyah Prof. Dr. Hamka, 2022)
Background: The mountain ecosystem in Mutis Timau Nature Reserve, Oelmuke Village, has a high diversity of flowering plants but has not been recorded. Inventaritation of the flowering plant provides reference information for area conservation. This study aims to inventory the types and uses of flowering plants by the community and other potential benefits in the Mutis Timau Nature Reserve, Oelmuke Hamlet, East Nusa Tenggara. Method: This research was conducted in August 2019 in Oelmuke Village, East Nusa Tenggara. The plant collection was conducted using an experimental method along the Oelmuke Village area. The information on the use of flowering plants by the community using the interview method and information about other potential uses using the literature review method. Result: The flowering plants inventoried from Oelmuke Village is 31 species from 15 families that have been used as food, animal feed, building materials, medicinal materials, ornamental plants, hedge plants, firewood, and cigarette raw materials, and textile materials. Other potential uses are as an accumulator of Pb waste and dye for woven fabrics. Conclusions: The 31 species of plants that have been inventoried have been used by the community as food, animal feed, building materials, medicinal materials, ornamental plants, hedges, firewood, cigarette raw materials, and textile materials and other potential uses are accumulator Pb waste and dyes for woven fabrics